(untitled) (Scientific journal of the Fergana State University, 2025)
In the article, the expression of the lyrical hero in children’s poetry, the expression of the poet himself or the role of a child played by the poet in accordance with their age and nature, is studied on the example of the work of Tursunboy Adashboyev, Abdurahmon Akbar and Dilshod Rajab. In children’s poetry, the lyrical hero is the image of a child, who differs in terms of age, and the manifestation of their characteristics, feelings, and thoughts specific to this period is analyzed on the basis of the comparative method.